Rahmat dan Bencana dalam Al-Qur’an: Studi Penafsiran Terhadap Qs. Al-Ahzab Ayat 17 Menurut Buya Hamka - Zainabila, Zainabila; Anwar, Husnel; Azmi Nasution, Ali (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In the Qur'an there are verses about mercy and disaster, one of which is in QS. Al-Ahzab verse 17. But these two words, namely mercy and disaster, many people still misunderstand the meaning of them. For example, when someone has an amputated hand. Hand amputation is bad, but behind it all there is good for him. If the community lacks understanding, then the community always thinks badly of what has happened, it is things like this that make the writer raise the theme of Grace and Disaster. Hamka with his Tafsir Al-Azhar is used as the primary reference. Based on this description, a problem formulation is taken, namely how is Hamka's interpretation of mercy and disaster in surah Al-Ahzab verse 17 in Tafsir al-Azhar?, and what is the relationship between mercy and disaster in improving the quality of life in this world and the hereafter. This research is a library research. According to Hamka, the results of the research obtained from research on mercy and disaster in the Qur'an, according to Hamka, are Rahmat according to buya Hamka in Tafsir Al-Azhar is a form of God's love for His servants that radiates to charity and deeds until one day he dies with husnul khatimah . Meanwhile, according to buya Hamka, disasters are divided into two, namely small disasters such as illness and major disasters that occur in the universe such as earthquakes, floods and volcanic eruptions. Buya Hamka also believes that the occurrence of disasters is caused by several factors, as mentioned in the Qur'an, namely the factor of human disbelief, the factor of human hypocrisy, and the factor of human disobedience.